Efektivitas Bimbingan Keagamaan Dalam Memfasilitasi Pemulihan Spiritual Narapidana Di Lembaga Pemasyarakatan (Lapas) Kelas Iia Banyuwangi - Iswatul Millah; Yohandi Yohandi; A. Husam Sulaiman (CV. SINAR HOWUHOWU, 2026)
Religious guidance is a form of development that plays an important role in the process of spiritual recovery for prisoners in correctional institutions. Prisoners, as individuals serving their sentences, often experience spiritual, psychological, and moral problems due to their past mistakes and the pressures of the prison environment. This study aims to understand the implementation of religious guidance and its role as a means of spiritual recovery for prisoners at Banyuwangi Class IIA Prison. The research method used is qualitative with a descriptive approach. Data collection was conducted through observation, interviews, and documentation. The results of the study show that religious guidance at Banyuwangi Class IIA Prison is carried out through various religious activities such as study groups, worship training, religious lectures, and moral development. These activities have a positive impact on the spiritual recovery of prisoners. which is marked by an increased religious awareness, inner peace, remorse for past actions, as well as a change in attitude and behavior for the better. Nevertheless, the implementation of religious guidance still faces several challenges, such as a limited number of mentors and supporting facilities. Therefore, efforts are needed to improve the quality of development so that religious guidance can be carried out more effectively and sustainably. Overall, religious guidance has proven to be an effective means of supporting inmates' spiritual recovery and preparing them to return to society as better individuals.